Perencanaan Tenaga Pendidik dan Kependidikan di Madrasah Tsanawiyah Nurun Nabi Al-Islami - Azmi, Fachruddin; Mesiono, Mesiono; Said, Salim; Muammar, Muammar (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Educational planning is a conscions effort and decision-making that has been carefully agread upon about things to be done in the future within a school instution for the purpose that have been planned beforehand. The reseach method used in this study is quantitative whit data collected using interviews, observation, and document, and documents. As for the qualifications regarding the results of reseach in the field regarding educator and educational planning at Madrasah Nurun Nabi Al-Islami, namely preparing teacher who have expertise in their scientific field, so that in carrying out the learning process teachers are expected to be able to convey material in accordance with learning objective, it is mandatory to be able to read the koran properly and correctly in terms of tajwid, makhrojil letters, educational staff who are in the madrasa are in the madrasa are dressed in Muslim and Muslim women. Keywords : Planning,Educator, Education